Analisis Sosiologi Sastra Dalam Novel Megat Karya Rida K Liamsi - Uchi Amelysa; Alfitriana Purba (LPPM STIKes SITI HAJAR dan Insight Power, 2021)
Sociology of literature is a research that examines the relationship of literary works with humans in society and their social processes. Megat novel by Rida K Liamsi contains many elements of sociology of literature, especially ethical, social, and cultural aspects. The research problems are (1) what are the ethical aspects in Rida K Liamsi's Megat novel, (2) what are the social aspects in Rida K Liamsi's Megat novel, (3) what are the cultural aspects in Rida K Liamsi's Megat novel. The purpose of this research is to find data and information about ethical, social, and cultural aspects in the novel Megat by Rida K Liamsi. This literary sociology research approach uses a qualitative approach to the type of library research. The method used is descriptive method. The data collection technique used is hermeneutic technique. The results of the research and the amount of data in Rida K Liamsi's Megat novel contain several ethical aspects, namely (1) ethics of responsibility 9 data, ethics of conscience 7 data, and ethics of rights and obligations 6 data. The ethical aspects contained in the novel Megat by Rida K Liamsi are reflected in the attitudes and behavior of the characters seen in the story. (2) The social aspects contained in Rida K Liamsi's Megat novel are social interaction 27 data, social group 2 data, and social conflict 4 data. The social aspect in Rida K Liamsi's Megat novel can be seen from the way the characters interact, group together, and the social conflicts contained in the novel. (3) The cultural aspects contained in Rida K Liamsi's Megat novel are language aspects 11 data, knowledge system 7 data, living equipment system and technology 9 data, living livelihood system 4 data, and religious system totaling 13 data from quotes in the novel Megat by Rida K Liamsi.Keywords: sociology of literature, ethics, social, culture